The Relationship Between Maternal Education Level and Infant Nutritional Status - Srikandi Potabuga; Nila Widya Keswara (Lembaga Pengembangan Kinerja Dosen, 2026)
Infant nutritional status is an important indicator of child health that is influenced by various factors, including maternal characteristics. Maternal education is often considered to play a role in determining infant care and feeding practices. This study aims to analyze the relationship between the mother's education level and infant nutritional status. The study uses a quantitative approach with a cross-sectional analytical observational design. The study sample consisted of 30 mothers and infants aged 0–12 months selected using purposive sampling. Maternal education level was categorized as elementary, secondary, and higher education, while infant nutritional status was determined based on anthropometric indicators according to WHO standards and the position of the Health Card (KMS). Data analysis was performed bivariately using Spearman's rho correlation test with a significance level of p < 0.05. The results of the study indicate that there is no significant relationship between the mother's level of education and the nutritional status of the infant (p = 0.575; r = −0.098). The correlation coefficient value indicates a very weak and statistically insignificant relationship. The conclusion of this study indicates that the mother's education level is not a factor directly related to the nutritional status of infants. The nutritional status of infants is likely to be more influenced by other more proximal factors, such as feeding practices, the quality and quantity of food intake, the child's health condition, and the family's environmental and socioeconomic factors.